PENGARUH MOTIVASI INSTRINSIK DAN EKSTRINSIK TERHADAP PRESTASI BELAJAR BAHASA INGGRIS MAHASISWA - Lestary, Mia (Universitas Mitra Indonesia, 2023)
Students are individuals who study within the scope of a university. A student who has motivation means that he has the power to achieve success in life. Motivation is very necessary in the activities of the teaching and learning process at school and also on campus. Students who have high motivation will be seen through their actions or activities in achieving achievement or learning goals. The purpose of this study is to determine the effect of intrinsic motivation and extrinsic motivation on students' learning achievement in English at Universitas Mitra Indonesia. The type of research used in this research is quantitative research. The population used is all students of Universitas Mitra Indonesia, Faculty of Business. The research sample obtained was 61 respondents. The data analysis tool uses research instrument tests, classical assumption tests and hypothesis testing. Based on the results of the research, Intrinsic Motivation and Extrinsic Motivation have a partial effect on Students' English Learning Achievement. The value of Fcount 282.153 3.16 Ftable. Thus, it can be concluded that the independent variables of Intrinsic Motivation and Extrinsic Motivation simultaneously or jointly affect the English Learning Achievement of Students at Mitra Indonesia University in Bandar Lampung. This shows that it means that Ha3 is accepted and Ho3 is rejected.